Analyzing the Reliability of Thesis Assessment Instruments: Generalizability Theory - Handayani, Reli; Ernanda, Ernanda; Rahariyoso, Dwi; Falani, Ilham; Oktadinata, Alek; Daya, Wawan Junresti; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to analyze the reliability of the thesis assessment instrument using Generalizability Theory (G-Theory).  This research is a quantitative study that applies G-Theory. G-Theory is unique and useful in evaluating the sources of actual variance and error in any measurement design. Thus, G-Theory contributes to improving reliability and validity in assessment. In this study, data were collected using a thesis assessment instrument that had been tested on thesis assessments conducted at the Faculty of Teacher Training and Education, Universitas Jambi.  G-Theory analysis in this study includes several main points, namely G-Study, Optimization (D-Study), and G-facets analysis. The results of the analysis show that the assessment instrument has a fairly high level of reliability with a G coefficient of 0.78. This indicates that the instrument can be used effectively in the thesis assessment. In addition, based on the results of the analysis carried out, recommendations were obtained to reassess item number two, increase the number of raters to six people to increase the reliability of the instrument to 0.80 to meet the satisfactory category. The resulting recommendations can be used by developers to improve the reliability of instruments in future assessment activities. This research is also expected to be a reference for future researchers in applying G-Theory in analyzing the reliability of measurement instruments.